Consumer Price Index (CPI) – Types & Sources - Ghodke, Mohammad; Giri, Purushottam (Indian Journal of Community Health, 2023)
The consumer price index is an important parameter to measure inflation. It reflects the relative changes in the prices of goods and services and its effect on inflation. These changes affect the real purchasing power of consumers and their welfare. It is used for regulation of wages, calculation of dearness allowance for workers and employees and for policy formations. Consumer price indices are of different types. Each type has its own significance. It is often difficult to identify the sources of consumer price indices and their specific uses.